POSTOPERATIVE COMPLICATIONS AND THEIR CORRELATION WITH THE SURGICAL TECHNIQUE IN THE TREATMENT OF GASTROSCHISIS - Kecman, Natalija; Milojković, Vesna (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Gastroschisis is a congenital paraumbilical defect of the anterior abdominal wall with evisceration of the abdominal organs. A modern approach to treating gastroschisis has contributed to better results, as evidenced by the 5% – 10% mortality rate. Aim: The study aims to evaluate the frequency of complications and death in the population due to gastroschisis, as well as the connection between the surgical techniques used in the treatment and the outcome of the treatment. Material and methods: The retrospective cohort study included 75 patients diagnosed with gastroschisis, treated from 2000 to 2020 at the Mother and Child Health Institute of Serbia Dr Vukan Čupić. By applying the exclusion criteria, a sample of 61 patients was obtained. Two cohorts of subjects were formed based on the applied surgical method, namely: primary repositioning and fascial closure of the defect (gastroschisis surgical cohort – GSC), i.e. delayed primary repositioning of the defect using a silastic bag (silastic gastroschisis cohort – SGC). Results: The gastroschisis surgical cohort comprised 38 patients, while the silastic gastroschisis cohort comprised 23 subjects. It was found that necrotizing enterocolitis (NEC) was a statistically significantly more frequent complication in subjects from the silastic gastroschisis cohort (5/23, i.e. 21.7% in SGC and 0/38 in GSC; RR 0.32, 95% CI: 0.22 – 0.47; p = 0.003). The statistical significance of the difference in relation to the frequency of other complications was not proven: ileus (0/23 in SGC and 5/38, i.e. 13.2% in GSC; RR 0.59, 95% CI: 0.47 - 0.73, p = 0.069), compartment syndrome (0/23 in SGC and 2/38, i.e. 5.3% in GSC; RR 0.61, 95% CI: 0.50 – 0.75, p = 0.263) and death ( 2/23, i.e. 8.7% in SGC and 2/38, i.e. 5.3% in GSC; RR 1.26, 95% CI: 0.46 – 3.43, p = 0.600). Conclusion: There is no distinctive proof of the superiority of one method over another. The risks of ileus and compartment syndrome are higher when applying primary fascial closure of the defect, while the risks of NEC and fatal outcome are higher when the silo method (use of a silastic bag, i.e., silo bag) is applied. The choice of method in treating gastroschisis depends on the abdominovisceral disproportion and the physical appearance of the eviscerated intestines, assessed with the Gastroschisis Prognostic Score (GPS).